Characterization of Homogeneous System of Difference Equations - Huda Hussein Abed; Bassam Jabbar Al-Asadi (Al-Mustansiriyah Journal of Science, 2021)
In this paper, we introduced new definitions of the system of homogenous difference equations of order two; namely homogenous and semi homogenous system, where we focused on finding the equivalents for these definitions of order one as well as of order greater than one for the system of difference equations of the second order and given some examples. We also a given formula to find the power of the matrix that we used in this research.